Decreased monsoon precipitation in the Northern Hemisphere due to anthropogenic aerosols. Issue 16 (19th August 2014) - Polson, D.; Bollasina, M.; Hegerl, G. C.; Wilcox, L. J.
Abstract The Northern Hemisphere monsoons are an integral component of Earth's hydrological cycle and affect the lives of billions of people. Observed precipitation in the monsoon regions underwent substantial changes during the second half of the twentieth century, with drying from the 1950s to mid‐1980s and increasing precipitation in recent decades. Modeling studies suggest that anthropogenic aerosols have been a key factor driving changes in tropical and monsoon precipitation. Here we apply detection and attribution methods to determine whether observed changes are driven by human influences using fingerprints of individual forcings (i.e., greenhouse gas, anthropogenic aerosol, and natural) derived from climate models. The results show that the observed changes can only be explained when including the influence of anthropogenic aerosols, even after accounting for internal climate variability. Anthropogenic aerosol, not greenhouse gas or natural forcing, has been the dominant influence on Northern Hemisphere monsoon precipitation over the second half of the twentieth century.